Building Science-Based Community Service Synergy, Specifically The Spreadsheets At Harapan Utama Vocational High School - Winda Lius; Kennardi Tanujaya (Universitas Internasional Batam, 2023)
Referring to Universitas Internasional Batam Higher Education, which includes education, research and community service, universities should be able to carry out this community service in a functional and integrated way. Community service as one of the pillars of higher education occupies a strategic position in community advancement and education to improve the community's quality of life. The form of coaching is considered the most what is realistic is nothing other than the provision of offerings through skills training and mentoring that are deemed useful to local community audiences. The Community Service Student Creativity Program is a means for students to fulfill the third mission of higher education, community service. The program that we propose this time has the title